In Pinochet S Shadows: The Incidence of Authoritarian/Democratic Values on the Vote Choice in the 2022 Constitutional Plebiscite in Chile - Osorio-Flores, R (CAMBRIDGE UNIV PRESS, 2025)
The transition to democracy in Chile, which took place under the rules established in the authoritarian constitution, led political parties and voters to align along an authoritarian/democratic divide. In the campaign for the constitutional plebiscite in 2022, some of those in favor of a new constitution linked their position to democratic values and labeled those opposed to the new draft as lacking democratic values. Many of those opposed to the new constitution purposely distanced themselves from the authoritarian legacy. We rely on a pre-electoral poll to explore democratic values in the vote choice in the plebiscite. When factoring for economic perceptions, ideological identification, and sociodemographic traits, while holding authoritarian values was positively associated with voting Reject, expressing democratic values had a weak association with voting Approve. The authoritarian/democratic divide in the party system in the early 1990s was not a relevant determinant of vote choice in the 2022 plebiscite.